Comparison of standard versus population-specific handgrip strength cut-off points in the detection of probable sarcopenia after launch of EWGSOP2. (4th December 2020) - Bahat, Gulistan; Kilic, Cihan; Altinkaynak, Mustafa; Akif Karan, Mehmet
Abstract: Objective: We aimed to compare European Working Group on Sarcopenia in Older People (EWGSOP2)-suggested and population-specific handgrip strength (HGS) thresholds to detect probable sarcopenia and their associations with physical-performance measures and frailty. Methods: A retrospective cross-sectional observational-study included geriatrics outpatients applied to a university-hospital. HGS, timed up and go test (TUG), and usual gait speed (UGS) were assessed. Frailty was screened by FRAIL-scale. Results: A total of 1825 older adults were included (mean age, 74.5 + 7.0 years; 68.8% female). Prevalence of low-HGS were 12.2% by the EWGSOP2-recommended (27/16 kg) cut-offs and 37.5% by population-specific cut-offs (35/20 kg) ( p <.001). When low-HGS was defined by EWGSOP2 suggested cut-offs, low-HGS was associated with impaired UGS, (odds ratio [OR] = 3.8, 95% confidence interval [CI]: 2.0–6.9, p <.001); impaired TUG, (OR = 4.6, 95% CI: 2.4–8.8, p <.001); and frailty (OR = 20.9, 95% CI: 8.3–53.0, p <.001). Similarly, low HGS determined by population-specific cut-off points was associated with impaired UGS (OR = 3.1, 95% CI: 2.1–6.9, p <.001); impaired TUG (OR = 6.0, 95% CI: 3.0–11.8, p <.001); and frailty (OR = 7.3, 95% CI: 4.1–13.0, p <.001). Conclusions: Application of EWGSOP2-recommended standard HGS-cut-offs showed successful application in-practice. However, use of standard HGS cut-offs may result in underdiagnosis of probable sarcopenia. Therefore, we suggest that, whenever available, use of population-specific cut-offs for HGS may be better for correctly identifying older adults at risk.